Efficacy, patient-reported outcomes, and safety of the anti-granulocyte macrophage colony-stimulating factor antibody otilimab (GSK3196165) in patients with rheumatoid arthritis: a randomised, phase 2b, dose-ranging study. (November 2020) - Buckley, Christopher D; Simón-Campos, Jesus A; Zhdan, Vyacheslav; Becker, Brandon; Davy, Katherine; Fisheleva, Elena; Gupta, Anubha; Hawkes, Carol; Inman, David; Layton, Mark; Mitchell, Nina; Patel, Jatin; et al.
Summary: Background: The human monoclonal antibody otilimab inhibits granulocyte-macrophage colony-stimulating factor (GM-CSF), a key driver in immune-mediated inflammatory conditions. We aimed to evaluate the efficacy, safety, and key patient-reported outcomes related to pain in patients with active rheumatoid arthritis receiving otilimab. Methods: This phase 2b, dose-ranging, multicentre, placebo-controlled study was done at 64 sites across 14 countries. Patients aged 18 years or older with rheumatoid arthritis who were receiving stable methotrexate were randomly assigned (1:1:1:1:1:1) to subcutaneous placebo or otilimab 22·5 mg, 45 mg, 90 mg, 135 mg, or 180 mg, plus methotrexate, once weekly for 5 weeks, then every other week until week 50. The randomisation schedule was generated by the sponsor, and patients were assigned to treatment by interactive response technology. Randomisation was blocked (block size of six) but was not stratified. Investigators, patients, and the sponsor were blinded to treatment. An unblinded administrator prepared and administered the study drug. The primary endpoint was the proportion of patients who achieved disease activity score for 28 joints with C-reactive protein (DAS28-CRP) <2·6 at week 24. Patients who were not in the otilimab 180 mg group, without a good or moderate European League Against Rheumatism response (week 12) or with DAS28-CRP >3·2 (week 24) escaped to otilimab 180 mg. Patients who escaped were treated as non-responders in their original assigned group. Safety endpoints were incidence of adverse events and serious adverse events, infections, and pulmonary events. Efficacy and safety outcomes were assessed in the intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT02504671 . Findings: Between July 23, 2015, and Dec 29, 2017, 222 patients were randomly assigned (37 to each group). 86 (49%) of 175 escaped to otilimab 180 mg at week 12 and 57 (69%) of 83 at week 24. At week 24, the proportion of patients with DAS28-CRP <2·6 was two (5%) of 37 in the otilimab 22·5 mg group, six (16%) of 37 in the 45 mg group, seven (19%) of 37 in the 90 mg group, five (14%) of 37 in the 135 mg group, five (14%) of 37 in the 180 mg, and one (3%) of 37 in the placebo group. The largest difference was achieved with otilimab 90 mg (16·2%; odds ratio [OR] 8·39, 95% CI 0·98–72·14; p=0·053). Adverse events were reported pre-escape in 19–24 (51–65%) patients and post escape in 10–17 (40–61%) patients across otilimab dose groups and in 18 (49%) of 37 and 22 (67%) of 33 in the placebo group. The most common adverse event was nasopharyngitis: 3–9 (8–24%) in otilimab groups and one (3%) in the placebo group pre-escape and 1–3 (4–10%) in otilimab groups and seven (21%) in the placebo group post escape. Pre-escape serious adverse events were foot fracture (otilimab 45 mg); arthralgia, myocardial infarction, dizziness (otilimab 90 mg); oesophageal spasm, acute pyelonephritis (otilimab 22·5 mg), and uterine leiomyoma (otilimab 135 mg). Post-escape serious adverse events were ankle fracture (placebo) and rheumatoid arthritis (otilimab 135 mg). There were no deaths or pulmonary events of clinical concern, and rates of serious infection were low. Interpretation: Otilimab plus methotrexate was well tolerated and, despite not achieving the primary endpoint of DAS28-CRP remission, there were improvements compared with placebo in disease activity scores. Of note, patients reported significant improvement in pain and physical function, supporting further clinical development of otilimab in rheumatoid arthritis. Funding: GlaxoSmithKline.